2007
DOI: 10.1111/j.1365-3113.2006.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Psephenidae (Coleoptera: Byrrhoidea) based on larval, pupal and adult characters

Abstract: Abstract. We conducted the first comprehensive phylogenetic analysis of Psephenidae, based on 143 morphological characters of adults, larvae and pupae and coded for 34 taxa, representing three outgroups and 31 psephenid genera, including four undescribed ones. A strict consensus tree calculated (439 steps, consistency index ¼ 0.45, retention index ¼ 0.75) from the two most-parsimonious cladograms indicated that the monophyly of the family and subfamilies is supported, with the exception of Eubriinae, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…No comprehensive phylogeny for Dryopidae or Elmidae has yet been undertaken. The phylogeny of Psephenidae was inferred based on adult morphology (Lee et al, 2007), and a new classification proposed. Recently, Jäch et al (2016) elevated Protelmini (a small group of about six described species from the Afrotropics and Neotropics) from a tribe of Elmidae to its own family, Protelmidae.…”
Section: Water Beetle Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…No comprehensive phylogeny for Dryopidae or Elmidae has yet been undertaken. The phylogeny of Psephenidae was inferred based on adult morphology (Lee et al, 2007), and a new classification proposed. Recently, Jäch et al (2016) elevated Protelmini (a small group of about six described species from the Afrotropics and Neotropics) from a tribe of Elmidae to its own family, Protelmidae.…”
Section: Water Beetle Phylogenymentioning
confidence: 99%
“…Although regional treatments and generic revisions exist to a certain extent for some groups, the recent publication of Miller & Bergsten's (2016) comprehensive resource on diving beetle biology and identification put into sharp relief the varying degrees to which water beetle identification is feasible. Of the 10 water beetle families with more than three described genera, modern global genus-level keys now exist for just half: Dytiscidae (Miller & Bergsten, 2016), Noteridae (Miller, 2009), Gyrinidae (Miller & Bergsten, 2012), Hydroscaphidae and Psephenidae (Lee et al, 2007). We still need comprehensive resources for the identification of Elmidae, Dryopidae, Hydraenidae and Hydrophilidae.…”
Section: Identification and Database Resourcesmentioning
confidence: 99%
“…In the recent phylogeny of the Psephenidae by Lee et al (2007), Neoeubria is included as "Genus A." In the most parsimonious tree Neoeubria is placed in a basal trichotomy within the subfamily Eubriinae.…”
Section: Key To Adults Of Neotropical Genera Of Eubriinaementioning
confidence: 99%
“…The family Psephenidae has experienced increased research interest and activity in the last decade or so, a major milestone of which was the publication of a phylogeny of the family by Lee et al in 2007. Much of the research has focused on the fauna of the Oriental and Australasian biogeographic zones, largely due to the studies of Chi-Feng Lee and colleagues who have described many new genera and an abundance of new species from that region (Lee & Jćch 1995;Lee & Yang 1996;Lee et al 1999Lee et al , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Essig (1926) reported underwater pupation by Eubrianax edwardsi (LeConte, 1874), though this was refuted by Brown (1987). However, underwater pupation by members of Psephenus Haldeman, 1853 and Psephenoides Gahan, 1914 has been repeatedly reported (Murvosh and Brown 1977;Murvosh 1993;Lee et al 2007). Although this study appears to be the first report of underwater pupation in Elmidae, it is likely that other species will be found that also exhibit this ability.…”
mentioning
confidence: 99%